2007
DOI: 10.1177/1476718x07076681
|View full text |Cite
|
Sign up to set email alerts
|

the realism and sex type of four- to five-year-old children's occupational aspirations

Abstract: Research on career development has focused primarily on adolescents and adults. However, in Gottfredson's theory of circumscription and compromise (2002) it is proposed that career aspirations originate in the preschool years and that the earliest work aspirations of children are sex typed in relation to the activities of same sex adults. This article investigates young children's career development in the context of Gottfredson's stage theory. Eighty-four children attending a kindergarten/early learning centr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 14 publications
1
11
0
Order By: Relevance
“…It seems likely that these children had some awareness of high visibility occupations like police officer, but little knowledge of lower visibility occupations like engineering technician. My findings are consistent with Gottfredson's theory and the findings of her previous studies (1981,2002), but they are inconsistent with the findings of Care et al (2007) that girls were less likely than boys to give fantasy responses. This may be the result of a group's idiosyncrasy or the small size of the sample in the study by Care and colleagues.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…It seems likely that these children had some awareness of high visibility occupations like police officer, but little knowledge of lower visibility occupations like engineering technician. My findings are consistent with Gottfredson's theory and the findings of her previous studies (1981,2002), but they are inconsistent with the findings of Care et al (2007) that girls were less likely than boys to give fantasy responses. This may be the result of a group's idiosyncrasy or the small size of the sample in the study by Care and colleagues.…”
Section: Discussionsupporting
confidence: 86%
“…In his theory of circumscription and compromise, Gottfredson (2002) proposes that occupational aspirations originate in the preschool years, and suggests that occupational aspirations should be viewed as an integral part of social development and identity. Since occupational aspirations can be viewed as attempts to construct a preferred self-image, if the self-image is shaped by unrealistic or unattainable perceptions, there will be repercussions for the individual (Care, Deans, & Brown, 2007).…”
mentioning
confidence: 99%
“…Some aspirations might be idealistic, abstract or hypothetical (with little thought for attainability), while other future pathways are held as concrete and achievable (Scanlon et al, 2008;Howley, 2009;Brown 2011). Research exploring children and young people's aspirations has tended to focus on educational aspirations (eg, Howley, 2009) or occupational aspirations (eg, Care et al, 2007). Strand and Winston's (2008) work summarises the many different influences shaping aspirations.…”
Section: Introductionmentioning
confidence: 97%
“…Schools, peer groups and broader media, institutional and cultural vehicles shape young people's inspirations (Strand and Wilson, 2008). Aspirations are also shaped by contextual factors (Hirschi, 2010), including gender (Care et al, 2007), class (Brown, 2011), ethnicity (DeWitt et al, 2013Strand and Winston, 2008) and disability (Scanlon et al, 2008).…”
Section: Introductionmentioning
confidence: 98%
“…However, the results of the research presented an inconsistent phenomenon. Research from Care et al (2007) demonstrated that four to five year old children of different genders had different career expectations and role playing abilities in fantasizing about the adult world. Low et al (2005) reported that in terms of career expectations, there was instability before one was 16 years old.…”
Section: Theories Related To Children's Career Expectationsmentioning
confidence: 99%